Adalimumab markedly improves enthesitis in patients with psoriatic arthritis: Evaluation with a magnetic resonance imaging scoring system. Issue 12 (24th June 2015) - Yanaba, Koichi; Sadaoka, Akari; Yonenaga, Takenori; Saeki, Hidehisa; Umezawa, Yoshinori; Tojo, Shinjiro; Ito, Toshihiro; Kikuchi, Sota; Fukuda, Kunihiko; Nakagawa, Hidemi
Abstract: Psoriatic arthritis (PsA), a seronegative arthropathy, may often result in progressive joint damage without treatment, leading to disability and impaired quality of life. Early therapeutic intervention of PsA is therefore crucial before the development of irreversible joint damage. Because psoriatic skin lesions generally precede the onset of PsA, dermatologists occupy an important position in treating patients with early PsA. This study aimed to evaluate the efficacy of adalimumab in treating joint disease in patients with PsA, using the PsA magnetic resonance imaging scoring system (PsAMRIS). Five adult Japanese male patients with active PsA were treated with adalimumab. Magnetic resonance imaging was obtained at baseline and 8–32 weeks with 2–3 time points following adalimumab treatment and assessed using PsAMRIS. Adalimumab treatment markedly improved clinical symptoms and disease activities of joint disease, which was confirmed by the reduction of PsAMRIS scores in all patients. Bone marrow edema and periarticular inflammation, reflecting the presence of enthesitis, were dramatically improved at week 8, while improvement of synovitis and flexor tenosynovitis was observed later, at week 24 or 32. However, bone erosion was not improved by adalimumab treatment during the follow‐up period. These results indicate that adalimumab treatment is associated with dramatic improvement of enthesitis in patients with PsA, whereas bone erosion may be resistant to such treatment. PsAMRIS appears to be useful for the evaluation of treatment efficacy in PsA.